Unruptured left cornual pregnancy with a high serum beta-hCG: a case report - Nirmala CK,; Lim PS,; Norzilawati MN,; Zainul RAZ,; Mohd. Hashim O, (Department of Surgery, UKM Medical Centre, 2011)
Ectopic pregnancy in the interstitial part of the fallopian tube (cornual pregnancy) is a rare condition but can be fatal. Traditionally, the treatment had been cornual resection or hysterectomy. More conservative approaches had been advocated recently. There is no consensus on the dose or number of methotrexate injections that should be used in the treatment of interstitial pregnancies. Single dose intramuscular methotrexate is one of the treatment options. However, the failure rate is higher if the serum -hCG (beta-human chorionic gonadotrophin) level is more than 5000 IU/L. We report a case of cornual ectopic pregnancy with high initial serum -hCG level being successfully treated with multiple doses of systemic methotrexate. MRI was used to assess clinical resolution of cornual ectopic pregnancy.